2021
DOI: 10.1093/intimm/dxab012
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of colonic inflammation by Lypd8 in a mouse model of inflammatory bowel disease

Abstract: Dysfunction of the intestinal mucosal barrier causes inflammatory bowel diseases (IBD). Indeed, mucosal barrier impairment in the gut of IBD patients results from decreased expression of barrier molecules. Lypd8 segregates microbiota from the colonic epithelial layer. In this study, we found that Lypd8−/− mice, in which flagellated bacteria invaded the mucosal surface of the colon, developed spontaneous colitis when dysbiosis was induced by a high-fat diet (HFD). Based on this finding, we assessed whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Lypd8 −/− mice show spontaneous inflammatory response than normal mice or high‐fat diet (HFD) mice. 34 Lypd8 gene is selectively expressed in the uppermost epithelial cells of the colorectal glands, possibly. It is in the Ly6/PLAUR domain containing eight (Lypd8) proteins, which can bind to the flagella of gram‐negative bacilli or Proteus mirabilis to inhibit the movement of the flagella, thereby preventing bacteria from entering the inner mucus layer, inhibiting the inflammatory response of epithelial cells, and separating bacteria and epithelial cell layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lypd8 −/− mice show spontaneous inflammatory response than normal mice or high‐fat diet (HFD) mice. 34 Lypd8 gene is selectively expressed in the uppermost epithelial cells of the colorectal glands, possibly. It is in the Ly6/PLAUR domain containing eight (Lypd8) proteins, which can bind to the flagella of gram‐negative bacilli or Proteus mirabilis to inhibit the movement of the flagella, thereby preventing bacteria from entering the inner mucus layer, inhibiting the inflammatory response of epithelial cells, and separating bacteria and epithelial cell layer.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that if Lypd8 gene expression is blocked, bacteria can directly bind to receptors on the cell membrane. Lypd8 −/− mice show spontaneous inflammatory response than normal mice or high‐fat diet (HFD) mice 34 . Lypd8 gene is selectively expressed in the uppermost epithelial cells of the colorectal glands, possibly.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the high expression of SLC26A3 could prevent DSS−induced acute colitis [ 58 ]. LYPD8 levels are significantly decreased in colitis patients, and supplementation of LYPD8 proteins might maintain colonic homeostasis in colitis patients by inhibiting the motility of pathogenic bacteria, such as γ-proteobacteria [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to FISH, the sections were treated with TrueBlack (Biotium Inc. Hayward, CA, USA) to reduce nonspecific fluorescence. Hybridization was conducted as described previously ( Hsu et al., 2021 ). Sections were incubated overnight at 40 °C with EUB338 probe or NON338.…”
Section: Methodsmentioning
confidence: 99%